Avicenna on Knowledge (ʿILM), Certainty (Yaqīn), Cause (ʿILLA/SABAB) and the Relative (MUḌĀF)1. Issue 3 (3rd May 2016) - Strobino, Riccardo
Abstract : In his Kitāb al-Burhān ( Book of Demonstration ), Avicenna discusses a theoretical framework broadly inspired by Aristotle's Posterior Analytics which brings together logic, epistemology and metaphysics. One of the central questions explored in the book is the problem of the relation between knowledge, certainty and causal explanation. Burhān 1.8, in particular, is devoted to the analysis of how certainty comes about in causal as opposed to non-causal contexts. The distinction is understood in Avicenna's system as one between cases in which the conclusion of an argument is warranted only in virtue of an appropriate middle term, and cases in which there is no such intermediary because the predicative link between subject and predicate of the conclusion is immediate. In this context, Avicenna makes use of the case of relative terms ( muḍāfāt ) to clarify certain crucial aspects of his theory. The paper explores this discussion and shows how Avicenna's account of the relatively marginal role of relatives in the context of demonstration depends on insights that are central to his metaphysics and epistemology.